MILLENNIAL DA'WAH INNOVATION OF PEMUDA HIJRAH LOMBOK IN DIGITAL DISRUPTION ERA - Sulastri, Leni; Kurniawan, Andri; Maliki, M. Irawan Imam (Universitas Islam Negeri Mataram, 2023)
We have seen far too many variations in millennial society's conduct, both positive and negative. In actuality, the excessive media consumption culture has an effect on abnormal conduct. Not to mention the issues with bullying and fake news that abound in online communities. This study aims to provide millennial society and da'wah actors with a reference while also learning about the da'wah innovative ideas of Pemuda Hijrah Lombok. This study combines library research with qualitative methodology. The research's findings point to the innovation of Pemuda Hijrah Lombok in the digital disruption era, particularly in the form of Deep Talk, Road Show, PHL, Journey with Al-Qur'an, and other constructive activities that help develop strong moral character and religious understanding. This initiative pushes netizens to adopt more sensible digital behavior.